2003
DOI: 10.1109/tsmcc.2003.818494
|View full text |Cite
|
Sign up to set email alerts
|

Materialized view selection as constrained evolutionary optimization

Abstract: Abstract-One of the important issues in data warehouse development is the selection of a set of views to materialize in order to accelerate a large number of on-line analytical processing (OLAP) queries. The maintenance-cost view-selection problem is to select a set of materialized views under certain resource constraints for the purpose of minimizing the total query processing cost. However, the search space for possible materialized views may be exponentially large. A heuristic algorithm often has to be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…Randomize algorithms such as simulated annealing algorithms [7,8,14] and genetic algorithms [5,13,18,30,16] have been used and explored for the selection of materialized views in order to improve the quality of the solution. These algorithms use a randomized search strategy for deciding which views to materialize.…”
Section: Randomized Algorithms Based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Randomize algorithms such as simulated annealing algorithms [7,8,14] and genetic algorithms [5,13,18,30,16] have been used and explored for the selection of materialized views in order to improve the quality of the solution. These algorithms use a randomized search strategy for deciding which views to materialize.…”
Section: Randomized Algorithms Based Methodsmentioning
confidence: 99%
“…We have implemented our approach and compared it with a randomized method because in previous studies [30,7,8], it was shown that randomized algorithms provide a significant improvement in the performance compared to deterministic algorithms. The most commonly used randomized algorithms in the context of view selection are simulated annealing algorithms and genetic algorithms.…”
Section: Experimental Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that evolutionary algorithms (EAs) are powerful techniques for solving various kinds of optimization problems in real-world applications [1,2]. Traditionally, researchers have been concentrating their attentions on EAs applied to stationary optimization problems, where problems are given in advance and maintain fixed during the evolutionary process.…”
Section: Introductionmentioning
confidence: 99%
“…fully used EAs in solving various kinds of problems in many fields [3], [21], [23], [36], [39]. Many scholars also concerned the related theoretical study of EAs.…”
mentioning
confidence: 99%